2017
DOI: 10.3389/fphys.2017.00178
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids Stimulate De novo Lipogenesis and Improve Glucose Homeostasis during Refeeding with High Fat Diet

Abstract: Aims: The recovery of body weight after a period of caloric restriction is accompanied by an enhanced efficiency of fat deposition and hyperinsulinemia—which are exacerbated by isocaloric refeeding on a high fat diet rich in saturated and monounsaturated fatty acids (SFA-MUFA), and poor in polyunsaturated fatty acids (PUFA), and associated with a blunting of de novo lipogenesis in adipose tissue and liver. As high fat diets rich in PUFA have been shown to limit the excess fat deposition and improve glucose hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…More than twenty years ago, it was reported that a diet enriched in PUFAs but otherwise normal with regards to total fat content increased both the level of UCP1 and the capacity for NST in murine interscapular BAT (iBAT) [13]. More recently, it was shown that refeeding rats a diet enriched in PUFAs, but not in saturated fatty acids, following two weeks of food restriction increased iBAT mass and expression of Ucp1 [14]. These findings suggest that PUFAs may improve the thermogenic capacity of BAT.…”
Section: Fish Oil and Thermogenic Adipose Tissuesmentioning
confidence: 99%
“…More than twenty years ago, it was reported that a diet enriched in PUFAs but otherwise normal with regards to total fat content increased both the level of UCP1 and the capacity for NST in murine interscapular BAT (iBAT) [13]. More recently, it was shown that refeeding rats a diet enriched in PUFAs, but not in saturated fatty acids, following two weeks of food restriction increased iBAT mass and expression of Ucp1 [14]. These findings suggest that PUFAs may improve the thermogenic capacity of BAT.…”
Section: Fish Oil and Thermogenic Adipose Tissuesmentioning
confidence: 99%
“…Studies on dietary restrictions have shown that altered meal pattern could be used to prevent certain metabolic diseases(28). Altered dietary may stimulate the mechanism against weight gain, fat accumulation, inflammation, glucose intolerance, insulin resistance, and loss of endurance and motor coordination(29). Our study reveals that refeeding from high-fat diet improves lipid homeostasis, which is seldom discussed by other researches.…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of fish oil had shown to increase UCP1 expression (Takahashi and Ide, 2000) and protein levels in interscapular BAT of rats (Kawada et al, 1998). Recently, dietary n-3 PUFAs has shown to lower the amount of visceral WAT and increase the mass of interscapular BAT in rats (Crescenzo et al, 2017).…”
Section: Fish-derived Omega-3 Fatty Acidsmentioning
confidence: 99%